Analisis Pengaruh Tingkat Suku Bunga, Inflasi, Nilai Tukar Terhadap Jumlah Uang Beredar di Indonesia Tahum 2009-2023 - Putra, Ahmad Dwi Afrizal; Winanto, Asis Riat; Abas, Sayid (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Abstract Employee performance is a vital aspect in determining the effectiveness and success of an organization, especially in the public sector. This study aims to analyze the effect of work engagement and work motivation on performance through organizational citizenship behavior (OCB). This study uses a quantitative method with a saturated sample technique of 121 employees in the public sector, the analyst uses the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method to test the relationship between variables. The findings of the study indicate that work engagement has a positive and significant effect on performance, but not significant on OCB. Work motivation has a positive and significant effect on performance and OCB. OCB has a positive and significant effect on performance. OCB cannot be a mediating role between work engagement and performance. However, it can be a mediating role between work motivation and performance. The implications of these findings suggest that organizations need to pay more attention to work motivation factors such as incentives, career development, and a supportive work environment, which can encourage higher OCB behavior, which ultimately contributes to improving overall employee performance. While work engagement has a direct impact on performance, organizations also need to find ways to enhance its impact on OCB to foster a more collaborative and productive work culture